Reina Lucía - Benson, E. F. (Edward Frederic), 1867-1940 (Impedimenta, 2013)
England between the wars was a paradise of utter calm and leisure for the very, very rich. But into this enclave is born Mrs. Emmeline Lucas -- La Lucia, as she is known -- a woman determined to lead a life quite different from the pomp and subdued and hushed nature of her class. With her cohort, Georgie Pillson, and her husband, Peppino, she upends the greats of high society: the imperious Lady Ambermere and her equally imperious dog, Pug; the odious Piggy and Goosie Antrobus; the Christian Scientist Daisy Quantrock, with her penchant for the foreign; and all the rest of Riseholme itself, the small English town just outside London that the British rich call their country home. Beset on all sides by pretenders to her social throne, Lucia rules her kingdom from the Hurst, Riseholme's greatest mansion, bringing culture, the fine arts, and a great deal of excitement and intrigue into this cloistered realm.